posted by .

Prove the identity.
6cos^2(x)-1 -12cos^4(x) +8cos^6(x)= cos^3(2x)

Thanks for your help :)

  • Trigonometry -

    Use the fact that
    cos(2x) = 2 cos^2 x - 1

    The left side of your identity is
    (2 cos^2x -1)^3
    Let's prove that:
    = (4 cos^4x -4 cos^2x +1)(2 cos^2x -1)
    = 8 cos^6x -12 cos^4x +6 cos^2 -1
    8 cos^6x -12 cos^4x +6 cos^2 -1
    = cos^3(2x)

  • Trigonometry -

    Thank you for your help :)
    By the way, i wanna ask which side i should start when i am asked to prove this boring identities and which formulae i should use. There r so many formulaes !!!! You know, i just dun have the "sense of mathematics". My friends can do this sum in 5 mins. I just cant figure how how he can do it.

  • Trigonometry -

    You can start on either side. It all depends upon which side already looks uncomplicated. Try simplifying the other side first. There is no single formula to use. Knowing the double angle formulas and the definitions if tan, cot, sec and csc in therms of sin and cos almost always helps.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Trigonometry

    Need help solving problems using the Trigonometric Identities: 8cos^4 thet=cos4theta+4cos2theta+3 I am a bit unsure how to solve it. I am aware that the first step I must take is to simplify the problem and then use the Product to …
  2. Math - Trig - Double Angles

    Prove: cos4x = 8cos^4x - 8cos^2x + 1 My Attempt: RS: = 4cos^2x (2cos^2x - 1) + 1 = 4 cos^2x (cos2x) + 1 LS: = cos2(2x) = 2cos^2(2x) - 1 = (cos^2(2)) - cos^2(2x)) - 1 ----- Prove: 8cos^4x = cos4x + 4cos2x + 3 My Attempt: RS: = cos2(2x) …
  3. Trigonometry

    Prove the identity sin(x+y+z)+sin(x+y-z)+sin(x-y+z)+ sin(x-y-z) = 4 sin(x)cos(y)cos(z) This identity is so long and after i tried to expand the left side and it just looked something crap Thanks for you help :)
  4. trigonometry

    2*cos^2(a/2)=(sin^2(a))/(1-cos(a)) can anyone help to prove this identity?
  5. Trigonometry

    1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two decimal places. 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y 10.Prove that 1+tanθ/1-tanθ = sec^2θ+2tanθ/1-tan^2θ 17.Prove that …
  6. Precalculus with Trigonometry

    Prove or disprove the following identity: cos (x+pi/6) +sin (x-pi/3) = 0
  7. Trigonometry desperate help, clueless girl here

    2. solve cos 2x-3sin x cos 2x=0 for the principal values to two decimal places. 3. solve tan^2 + tan x-1= 0 for the principal values to two decimal places. 4. Prove that tan^2(x) -1 + cos^2(x) = tan^2(x) sin^2 (x). 5.Prove that tan(x) …
  8. math trigonometry

    Prove the identity Sin^3X sinx*cos^2X=tanx/cosX
  9. math trigonometry

    Prove the identity Sin^3X+sinx*cos^2X=tanx/cosX
  10. math help trigonometry

    Prove the following identity tan x cos x/sin x=1/sin x cos x

More Similar Questions